PERAN KEPALA DESA DALAM PEMBANGUNA DESA GOSOMA KECAMATAN TOBELO KABUPATEN HALMAHERA UTARA PROVINSI MALUKU UTARA - BAGALI, PRISKA; ROMPAS, WELSON; RURU, JOORIE (JURNAL ADMINISTRASI PUBLIK, 2018)
Based on Law No. 6 of 2014 on the village articles 78, paragraph one and two, village development aims toimprove the welfare of rural communities and quality of life.Human and poverty reduction through the fulfillment of basic needs, development of village facilities andinfrastructure, development of local economic potential, and sustainable use of natural resources andenvironment. Village development as referred to in paragraph two promotes togetherness, kinship and mutualcooperation in order to realize the mainstreaming of peace and social justice.This research uses qualitative method in accordance with title and problem of purpose of this research is toknow how role of head of village leadership in development in Gosoma village and to know role of leadershipfrom village head in completing development even though lack of human resources and personal problem.Keywords: leadership role, village head and development